2020
DOI: 10.1037/bne0000402
|View full text |Cite
|
Sign up to set email alerts
|

Acute NMDA receptor antagonism impairs working memory performance but not attention in rats—Implications for the NMDAr hypofunction theory of schizophrenia.

Abstract: Cognitive deficits in schizophrenia, which include impairments in working memory and attention, represent some of the most disabling symptoms of this complex psychiatric condition, and lack effective treatments. NMDA receptor (NMDAr) hypofunction is a strong candidate mechanism underlying schizophrenia pathophysiology, and has been modeled preclinically using acute administration of NMDAr antagonists to rodents to investigate biological mechanisms underpinning cognitive dysfunction. However, whether and how NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Although KYN itself does not directly excite or inhibit neural activity, the downstream metabolites of KYN, quinolinic acid and 3-HK, are known to have N-methyl-D-aspartate (NMDA) receptor agonist effects, while KYNA is known to have NMDA receptor antagonist effects 50 . The balance of both affects neural activity via NMDA receptors 51 , and therefore, it may be related to brain functions, such as attention and working memory, in which NMDA receptors play an important role [52][53][54][55] . In the DLPFC, a brain region important for working memory and attention, NMDA receptors are known to be involved in attention and working memory by activating pyramidal cells to re synapses persistently 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Although KYN itself does not directly excite or inhibit neural activity, the downstream metabolites of KYN, quinolinic acid and 3-HK, are known to have N-methyl-D-aspartate (NMDA) receptor agonist effects, while KYNA is known to have NMDA receptor antagonist effects 50 . The balance of both affects neural activity via NMDA receptors 51 , and therefore, it may be related to brain functions, such as attention and working memory, in which NMDA receptors play an important role [52][53][54][55] . In the DLPFC, a brain region important for working memory and attention, NMDA receptors are known to be involved in attention and working memory by activating pyramidal cells to re synapses persistently 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…The length of the session has previously been set at a shorter time of 30 min/session, requiring the completion of 60 trials during a session (Oomen et al, 2013). The short session length contrasts with researchers who have doubled the session length but have maintained a relatively low number of required trials, 64 trials in 60 min (Lee et al, 2020). This protocol mirrors the general ratio of 1-2 trials/min by requiring the rats to reach the criterion of 84 trials in 60 min, which has been previously found to be successful (Anderson et al, 2020;Davies et al, 2017;Scott et al, 2019;Scott et al, 2021).…”
Section: Critical Parametersmentioning
confidence: 99%
“…The approach described in this protocol aligns with substage c, as a reward pellet is only delivered when the correct light stimulus is selected; otherwise, no response is observed. The rats can progress to the next substage when they reach the expressed criterion (Lee et al., 2020; Oomen et al., 2013). The length of the session has previously been set at a shorter time of 30 min/session, requiring the completion of 60 trials during a session (Oomen et al., 2013).…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations